Tetrachyron omissum y Trigonospermum alexandri, dos especies nuevas de Compositae-heliantheae del centro de México - Rzedowski, Jerzy; Calderón de Rzedowski, Graciela; Pérez-Calix, Emmanuel (Instituto de Ecología, A.C., 2008)
Tetrachyron omissum and Trigonospermum alexandri are illustrated and described as new species. The first grows in northeastern Querétaro and is related to T. websteri (Wussow & Urbatsch) B. L. Turner. The second is an aquatic or subaquatic plant known only from two pools in the vicinity of the town of Santa Clara del Cobre in northern Michoacán. It is possibly related to T. adenostemoides Less.